NIGHTMARES FROM TOPICAL TIMOLOL EYE DROPS: A CASE REPORT - Yousaf Jamal Mahsood (Khyber Medical University Journal, 2020)
Topical timolol eyedrops are frequently used as medical treatment of glaucoma. They decrease the production of aqueous humor by blocking the beta adrenergic receptors of ciliary body. Although systemic absorption of eyedrops is negligible, still it can cause some serious side effects like bradycardia, heart block, bronchospasm, confusion and hypotension. We present a case who developed nightmares with use of topical beta-blockers. He was a chronic case of primary open angle glaucoma whose target intraocular pressure (IOP) couldn’t be achieved with latanoprost alone, the first line drug, so we put him on topical timolol twice daily dosage to further decrease the IOP. On his follow-up visit he complained about bad dreams since starting timolol eye drops. This case report will add to the list of already known other side effects of timolol usage in glaucoma patients.